2016
DOI: 10.1016/j.homp.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Open-label observational study of the homeopathic medicine Passiflora Compose for anxiety and sleep disorders

Abstract: Anxiety and/or SDS improved significantly in patients included on this study. PC could be an alternative to the use of psychotropic drugs for first intention treatment of anxiety and SDS. Further studies are needed to confirm those results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Several herbs have been reported to have a sedative or sleep-promoting capacity: valerian (Valeriana officinalis), hops (Humulus lupulus), German chamomile (Matricaria recutita), passionflower (Passiflora incarnata), and Polygonatum sibiricum. [12][13][14][15] Our previous study revealed that the mixture of Lactuca sativa and skullcap extracts played an active role in sleep promotion. 16) In this study, we focus on the sleep-promoting effect of romaine lettuce and its mechanisms by investigating antagonistic behaviors on sleep-related receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Several herbs have been reported to have a sedative or sleep-promoting capacity: valerian (Valeriana officinalis), hops (Humulus lupulus), German chamomile (Matricaria recutita), passionflower (Passiflora incarnata), and Polygonatum sibiricum. [12][13][14][15] Our previous study revealed that the mixture of Lactuca sativa and skullcap extracts played an active role in sleep promotion. 16) In this study, we focus on the sleep-promoting effect of romaine lettuce and its mechanisms by investigating antagonistic behaviors on sleep-related receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicine is one of the most frequently used interventions for the treatment of insomnia for thousands of years (Shi et al, 2014). For instance, valerian (Valeriana officinalis) roots, alone or in combination with hops (Humulus lupulus L.), chamomile (Matricaria chamomilla), and passion flower (Passiflora), has been used as calming and sleep-promoting herbs (Abourashed et al, 2004;Srivastava et al, 2010;Villet et al, 2016). These herbal treatments have been reported to induce sedative effects via c-aminobutyric acid-ergic (GABAergic) or serotonergic neurotransmission regulation in animals and humans (Attele et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Enquanto pacientes diagnosticados com sintomas mais graves foram orientados a usar tanto o fitoterápico quanto psicotrópicos. Todavia, a melhora da ansiedade e dos distúrbios do sono foram estatisticamente mais favoráveis para pacientes que fizeram uso apenas da P. incarnata, embora os que a utilizavam isoladamente ainda apresentassem sintomas mais leves (Villet et al, 2016).…”
Section: Fonte: Autores (2022)unclassified